IMPLEMENTATION OF SYMBOLIC MODELING TECHNIQUES TO INCREASE ENTREPRENEURIAL MOTIVATION IN VOCATIONAL SCHOOL STUDENTS - Wildan Muhammad Wildan Ihsani; Ade Irma Noviyanti; Bhennita Sukmawati (EDUCATIONE, 2026)
Entrepreneurial motivation is a key factor in preparing vocational students to become independent and competitive in the world of work. This study aimed to analyze the effectiveness of symbolic modeling techniques in individual counseling services to enhance entrepreneurial motivation among vocational school students. The research employed a qualitative case study design with two twelfth-grade students from the Digital Business Department of Kartini Vocational High School, Jember, who were purposively selected for having low entrepreneurial motivation. Data were collected through observations, semi-structured interviews, documentation, and field notes, using video-based symbolic modeling of entrepreneurial role models as the intervention medium. The data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing/verification, with triangulation applied to ensure validity. The results showed that both students demonstrated significant improvement in entrepreneurial motivation across Bandura’s four stages of modeling: attention, retention, reproduction, and motivation. The first student developed a realistic small-scale business plan with optimism and family support, while the second student presented ambitious entrepreneurial ideas but faced doubts regarding financial feasibility. Overall, the findings confirmed that symbolic modeling strengthened students’ self-confidence, perseverance, initiative, and willingness to take risks. These outcomes support Bandura’s social cognitive theory and Ryan’s self-determination theory, highlighting the role of observation, self-efficacy, and intrinsic motivation in fostering entrepreneurial readiness. This study concludes that symbolic modeling is an effective counseling strategy for enhancing entrepreneurial motivation and offers practical implications for counselors, teachers, and future research in vocational education.